Energy dissipation in driven granular matter in the absence of gravity - Sack, Achim; Heckel, Michael; Kollmer, Jonathan; Zimber, Fabian; Pöschel, Thorsten (Physical Review Letters, 2013)
We experimentally investigate the energy dissipation rate in sinusoidally driven boxes which are partly filled by granular material under conditions of weightlessness. We identify two different modes of granular dynamics, depending on the amplitude of driving, A. For intense forcing, A>A, the material is found in the collect-and-collide regime where the center of mass of the granulate moves synchronously with the driven container, while for weak forcing, A